Black: A Persuasive Metaphor in Guinness Stout’s Advertisements in Nigeria - Dalamu, Taofeek Olaiwola (Revista de Humanidades, 2020)
Abstract: This study investigated the terminology of Black as a career metaphor that promotes the image of Guinness®. Thus, six ads of Guinness, deploying Black as the hub, were selected for illustrations. The author adopted Lakoffian-Johnsonian concept of metaphor supported with the Hallidayan mood system for the analysis. As Guinness embraces qualities of Black as its stronghold-cum-primary source domain, the study revealed the model as being very distinct. Black attributes, propagated as fashionable, beautiful, sophisticated, kingly, famous, etc., facilitate readers to consumption by seducing the audience to perceive Guinness as personified Black that must be admired. Black is no more a derogatory color concept as a coinage of colonial mastery. It is exalted as an important object of identification that sponsors the globally-renowned Guinness. The study suggested that researchers should not perceive Black as only synonymous to Guinness, but should serve as an approach to influence their communication choices and styles. Resumen: Este estudio se centra en el uso del término Black como una metáfora de la imagen de Guinness®. De esta forma, seis anuncios de Guinness utilizan la idea de Black como imagen de sus campañas publicitarias. El autor emplea el concepto de metáfora desarrollado por Lakoff y Johnson apoyado sistema tripartito de Halliday. A medida que Guinness adopta las cualidades de Black como su dominio fuente de fortaleza-primaria, el estudio reveló que el modelo es muy distinto. Los atributos de “negros”, como sinónimos de elegantes, hermosos, sofisticados, reales, famosos, etc., facilitan el consumo de los lectores seduciendo al público que percibe a Guinness como un negro personificado que debe ser admirado. El “negro” ya no es un concepto de color despectivo invención del dominio colonial. Es exaltado como un importante objeto de identificación que patrocina a Guinness, de renombre mundial. El estudio sugirió que los investigadores no deberían percibir a Black solo como un sinónimo de Guinness, sino que debería servir como un enfoque para influir en sus elecciones y estilos de comunicación.